Respon Pertumbuhan Bibit Kakao (Theobroma cacao L.) Terhadap Pemberian Kompos Limbah Kelapa Sawit - Fico Ovender; Rudi Hartawan; Edy Marwan (Universitas Batanghari, 2021)
Cacao (Theobroma cacao L.) is one of the important plantation commodities after oil palm and rubber. This plant has a high economic value and is a foreign exchange earner. The seeds produced are used as raw material for the foodstuff industry as well as for the pharmaceutical and cosmetic industries. Based on data from the Central Statistics Agency, the productivity of cocoa-farmers in Jambi is still very low, only reaching 585 kg ha-1. This study aims to obtain a dose of oil palm waste compost to support the growth of cocoa seedlings. The experiment was carried out in Pijon Village, Jaluko District, Muaro Jambi Regency from December 2020 to April 2021. This experiment was carried out using a completely randomized design environment. The treatment design used was compost dosage consisting of 4 levels, namely p0 = without giving compost, p1 = 5 tons ha-1 (7.5 grams per 3 kg of media), p2 = 10 tons ha-1 (15 grams per 3 kg of media) and p3 = 15 tons ha-1 (22.5 grams per 3 kg of media). The observed data were tabulated and analyzed with analysis of variance. If the calculated F value has a significant effect, then the DNMRT further test for 95% accuracy is carried out. The results showed that the application of compost 15 tons ha-1 showed an increase the plant height of 63.78%, the stem diameter of 73.68%, the shoot dry weight 30.83%, the total dry weight 95.12%, an the short root ratio 90.37%.